2014
DOI: 10.1158/1535-7163.mct-14-0147
|View full text |Cite
|
Sign up to set email alerts
|

Delineating the mTOR Kinase Pathway Using a Dual TORC1/2 Inhibitor, AZD8055, in Multiple Myeloma

Abstract: Despite promising preclinical results with mTOR kinase inhibitors in multiple myeloma, resistance to these drugs may arise via feedback activation loops. This concern is especially true for insulin-like growth factor 1 receptor (IGF1R), because IGF1R signaling is downregulated by multiple AKT and mTOR feedback mechanisms. We have tested this hypothesis in multiple myeloma using the novel selective mTOR kinase inhibitor AZD8055. We evaluated p-mTOR S 2481 as the readout for mTORC2/Akt activity in multiple myelo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 24 publications
(40 reference statements)
0
15
0
Order By: Relevance
“…While these drugs inhibit only mTORC1 and lead to activation of Akt due to negative feedback of mTORC2 [77], dual inhibition of mTORC1 and mTORC2 in MM cells demonstrates significant growth inhibition [78]. Moreover, dual inhibition of PI3K/mTOR or insulin-like growth factor 1 receptor (IGF1R)/mTOR also triggers significant anti-tumor effects in MM [79, 80]. …”
Section: Targeting Signal Transductionmentioning
confidence: 99%
“…While these drugs inhibit only mTORC1 and lead to activation of Akt due to negative feedback of mTORC2 [77], dual inhibition of mTORC1 and mTORC2 in MM cells demonstrates significant growth inhibition [78]. Moreover, dual inhibition of PI3K/mTOR or insulin-like growth factor 1 receptor (IGF1R)/mTOR also triggers significant anti-tumor effects in MM [79, 80]. …”
Section: Targeting Signal Transductionmentioning
confidence: 99%
“…This is especially so since previous work has demonstrated anti-MM efficacy of dual TORC1/TORC2 inhibitors (28) as well as AKT inhibitors (29). However, several studies (1, 5) clearly demonstrate that the adverse effect of DEPTOR gene silencing in MMCLs is prevented by RAPTOR knockdown, thus implicating TORC1 activation.…”
Section: Discussionmentioning
confidence: 95%
“…In vitro and in vivo studies showed that dual mTORC1/C2 inhibitor is more active against myeloma cells than mTORC1 inhibition alone (rapamycin) that could results in the feedback activation of AKT [27, 46]. But one major weakness of mTORC1/C2 inhibitor treatment is that it induces upregulation of IGF-1 receptor phosphorylation in MM cell lines, which rescues myeloma cells from apoptosis despite mTOR kinase inhibition and mTORC2/AKT blockage [47]. Given these observation and the fact that exogenous IGF-1 did not reverse GSK-470-induce cell death and GSK-470 could not inhibit mTORC2, there is a need to combine dual mTORC1/C2 inhibitor with GSK-470 to target and overcome these resistance mechanisms.…”
Section: Discussionmentioning
confidence: 99%